Abemaciclib induces atypical cell death in cancer cells characterized by formation of cytoplasmic vacuoles derived from lysosomes - Hino, Hirotsugu; Iriyama, Noriyoshi; Kokuba, Hiroko; Kazama, Hiromi; Moriya, Shota; Takano, Naoharu; Hiramoto, Masaki; Aizawa, Shin; Miyazawa, Keisuke (Cancer science, 2020)
In the cell cycle, the G1/S transition is controlled by the cyclin‐dependent kinase (CDK) 4/6‐cyclin D complex. Constitutive activation of CDK4/6 dysregulates G1/S transition, leading to oncogenic transformation. We found that 3 CDK4/6 inhibitors, abemaciclib, ribociclib, and palbociclib, exerted a cytocidal effect as well as a cytostatic effect at the G1 phase in cancer cell lines, including A549 human non–small cell lung cancer cells. Among these inhibitors, abemaciclib exhibited the most potent cytotoxic effect. The cell‐death phenotype induced by abemaciclib, which entailed formation of multiple cytoplasmic vacuoles, was not consistent with apoptosis or necroptosis. Abemaciclib blocked autophagic flux, resulting in accumulation of autophagosomes, however vacuole formation and cell death induced by abemaciclib were independent of autophagy. In addition, methuosis, a cell‐death phenotype characterized by vacuole formation induced by excessive macropinocytosis, was excluded because the vacuoles did not incorporate fluorescent dextran. Of note, both formation of vacuoles and induction of cell death in response to abemaciclib were inhibited by vacuolar‐type ATPase (V‐ATPase) inhibitors such as bafilomycin A1 and concanamycin A. Live‐cell imaging revealed that the abemaciclib‐induced vacuoles were derived from lysosomes that expanded following acidification. Transmission electron microscopy revealed that these vacuoles contained undigested debris and remnants of organelles. Cycloheximide chase assay revealed that lysosomal turnover was blocked by abemaciclib. Furthermore, mTORC1 inhibition along with partial lysosomal membrane permeabilization occurred after abemaciclib treatment. Together, these results indicate that, in cancer cells, abemaciclib induces a unique form of cell death accompanied by swollen and dysfunctional lysosomes. We found that abemaciclib, a CDK4/6 inhibitor, exerted a potent cytocidal effect in cancer cell lines with an atypical cell death phenotype, which entailed formation of multiple cytoplasmic vacuoles, and both the formation of vacuoles and the induction of cell death were inhibited by V‐ATPase inhibitors. Precise live‐cell imaging and transmission electron microscopy revealed that these vacuoles were derived from lysosomes that expanded following acidification and contained undigested debris and remnants of organelles. Thus we here propose a unique form of cell death accompanied by swollen and dysfunctional lysosomes by abemaciclib treatment.